Microstructural characterization and mechanical integrity of stainless steel 316L clad layers deposited via wire arc additive manufacturing for nuclear applications. Issue 6 (16th June 2021) - Kannan, A. Rajesh; Kumar, S. Mohan; Pramod, R.; Shanmugam, N. Siva; Vishnukumar, M.; Naveenkumar, S.
Abstract: The potential applications of stainless steel 316L components using wire arc additive manufacturing offers many benefits such as improved part complexity, higher deposition rate and less material waste. Microstructural examination indicates the strong interlayer bonding between cladded layers and was mainly austenitic with columnar and equiaxed dendrites while equiaxed grains with annealing twins were observed in the stainless steel 316L substrate. In the current study, we report that stainless steel 316L additively cladded via wire arc additive manufacturing exhibits a 11 % and 14 % increase in the yield strength and tensile strength, correspondingly in contrast to the stainless steel 316L substrate. The enhanced mechanical properties are attributed to the columnar structure and interlayer remelted peritectic growth. Hardness values were higher at the cladded layers compared to the interface and substrate. Interface sample failed in the substrate side and all samples exhibited ductile mode of fracture with fine dimples and micro voids. Wire arc additive manufacturing process can be employed for producing or repairing components with better mechanical properties and corrosion performance for elevated temperature environments including nuclear reactor applications. Abstract : In this study the microstructural features and mechanical properties of cladded austenitic stainless steel layers deposited by wire arc additive manufacturing were analyzed. This work demonstrates the advantages of wire arc additive manufacturing process for manufacturing or repairing medium and large structures.